2003
DOI: 10.1007/s10265-003-0085-7
|View full text |Cite
|
Sign up to set email alerts
|

Carbon autonomy of reproductive shoots of Siberian alder ( Alnus hirsuta var. sibirica )

Abstract: Carbon autonomy of current-year shoots in flowering, and of current-year shoots plus 1-year-old shoots (1-year-old shoot system) in fruiting of Siberian alder (Alnus hirsuta var. sibirica) was investigated using a stable isotope of carbon, (13)C. The current-year shoot and 1-year-old shoot systems were fed (13)CO(2) and the atom% excess of (13)C in flowers and fruits was determined. The majority of photosynthate allocated to flower buds was originally assimilated in the leaves of the flowering current-year sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 32 publications
2
45
1
1
Order By: Relevance
“…The link between carbon, nutrient, and water fluxes in the autonomy of twigs in trees has been widely discussed but it has never been linked directly to bud break especially in deciduous trees which are supposed to heavily rely on stored carbon reserves during this process (Dickmann and Kozlowski 1970;Gordon and Larson 1970). Until now the carbon autonomy of shoots and branches in deciduous trees through the bud break phase has only been suggested (Landhäusser and Lieffers 2003;Marchi et al 2005;Schädel et al 2009); however, there has been some other empirical evidence for carbon autonomy of branches during the flower and fruit production in several species of trees and shrubs (Hasegawa et al 2003;Hoch 2005;Hoch and Keel 2006;Volpe et al 2008).…”
Section: Discussionmentioning
confidence: 97%
“…The link between carbon, nutrient, and water fluxes in the autonomy of twigs in trees has been widely discussed but it has never been linked directly to bud break especially in deciduous trees which are supposed to heavily rely on stored carbon reserves during this process (Dickmann and Kozlowski 1970;Gordon and Larson 1970). Until now the carbon autonomy of shoots and branches in deciduous trees through the bud break phase has only been suggested (Landhäusser and Lieffers 2003;Marchi et al 2005;Schädel et al 2009); however, there has been some other empirical evidence for carbon autonomy of branches during the flower and fruit production in several species of trees and shrubs (Hasegawa et al 2003;Hoch 2005;Hoch and Keel 2006;Volpe et al 2008).…”
Section: Discussionmentioning
confidence: 97%
“…Shoot dynamics and reproductive output At a glance, it may be thought to be a good strategy to repeat high reproductive output every year, since the reproductive tissues of Siberian alder are produced mainly with current photosynthate, not stock (Hasegawa et al 2003). However, the results of the matrix simulation showed that the current-year shoot population of Siberian alder yields more reproductive output when they repeat reproductive and explorative regime reciprocally, than repeat only the productive regime every year (Fig.…”
Section: Annual Change Of Shoot Dynamicsmentioning
confidence: 81%
“…The predator-saturation hypothesis does not seem to explain the annual variation of reproductive output in Siberian alder because the seeds are very tiny and predation does not seem to cause negative effects on regeneration. The resource-budget model is not consistent with the situation in Siberian alder because current photosynthate is mainly allocated to make flower buds and to mature fruits in Siberian alder as shown by Hasegawa et al (2003) with a 13 C tracing experiment. The resource-matching hypothesis also does not seem to explain the annual variation for the same reason as for the resource-budget model.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, considering the total amount of available resources at the level of individual tree is meaningless, because the resources produced by the leaves of the current-year shoot are allocated to the reproductive tissues on the current-year shoots in Siberian alder (Hasegawa et al 2003). Thus, we expected that the floral sex allocation at the level of current-year shoots may depend on the amount of resource in the current-year shoots; however, no significant relationships between the amount of resources and floral sex allocation at the level of current-year shoot were found.…”
Section: Sex Allocation At the Level Of Current-year Shootsmentioning
confidence: 99%